Segmentasi Tingkat Pemakaian Material dengan Data Mining Clustering - Nurul Azwanti (Politeknik Caltex Riau, 2018)
Technology that plays an active role in human activities is communication technology that we can find on mobile devices or computers that have internet access. PT. Telkom Akses Kantor Telkom Marina is a subsidiary of PT Telekomunikasi Indonesia Tbk (Persero) commonly called Telkom Indonesia or Telkom which is the largest information and communication company and telecommunications service and network provider in Indonesia. Located in the Riau Islands region, precisely Batam City provides job services for Installing New Channels (PSB) such as installation of internet, telephone, cable TV, and maintenance in fiber optic networks both in residential areas, buildings, shop houses and malls with distribution of Sagulung, Lubuk Baja and Batam Center. PT. Telkom Telkom Akses Kantor Telkom Marina has difficulty in meeting the minimum stock of each material based on the request for use of the distribution area. From the data on the use of existing material, it is only used for recording material usage only, while stored data is never reprocessed. Evaluation of segmentation / mapping is very important to find out whether the needs really have been met. The results of this study are expected to be able to cluster data on material usage data and the use of the K-Means method to provide results overview for material usage segmentation. The goal is for companies to be able to do and increase inventory of materials that are often ordered for each region. Keywords: segmentation, usage, material, k-means